Facultative asexual reproduction and genetic diversity of populations in the humivorous termite Cavitermes tuberosus - Fournier, Denis; Hellemans, Simon; Hanus, Robert; Roisin, Yves (Proceedings. Biological sciences, 2016)
Termite colonies are typically founded by a pair of sexually reproducing dispersers, which can sometimes be replaced by some of their offspring. Some Reticulitermes and Embiratermes species routinely practice asexual queen succession (AQS): the queen is replaced by neotenic daughters produced by parthenogenesis, which mate with the primary king. Here, to cast light on the evolution of AQS, we investigated another candidate species, Cavitermes tuberosus (Termitinae). Of 95 nests, 39 contained a primary queen and 28 contained neotenic females (2-667 individuals), usually with the primary king. Microsatellite analyses confirmed that colonies were initiated by single pairs after large dispersal flights. More than 80% of the neotenic females were of exclusively maternal origin and completely homozygous, suggesting automictic parthenogenesis with gamete duplication. Conversely, workers, soldiers, and most alates and primary reproductives were produced sexually. AQS often occurs late, after colonies have reached maturity, whereas early AQS in other species may boost the young colony's growth rate. We suggest additional benefits of AQS in C. tuberosus, related with a smaller size, lesser stability and higher mobility of colonies. Our data add to the phylogenetical dispersion and diversity of modalities of AQS in termites, supporting a multiple evolutionary origin of this process.
Keywords: Isoptera; Termitidae; reproductive strategies; population structure; gamete duplication; partenogeneze; Parthenogenesis; Animals; Genetic Variation; Female; ženské pohlaví; thelytokous parthenogenesis; genetická variace; zvířata